Identifikasi Karakteristik dan Pengetahuan Lokal Nelayan Ikan Terubuk di Pulau Bengkalis Provinsi Riau - Djunaidi, Djunaidi; Kelana, Perdana Putra; Pramesthy, Tyas Dita; Nur Arkham, Muhammad; Rangga Bayu Kusuma Haris (Cenderawasih University, 2023)
Fishermen play a crucial role in the 2016 national action plan for terubuk. Accordingly, conducting a study on fishermen is imperative. The primary objective of this research is to discern the characteristics and knowledge of local fishermen pertaining to terubuk. The employed method involved conducting interviews with 30 fishermen who specialize in catching terubuk. The collected data underwent descriptive quantitative analysis. The research findings revealed that all respondents were within the productive age range, and those engaged in supplementary occupations outnumbered the Bengkalis minimum salary. Local respondents exhibited a commendable level of knowledge, demonstrating an ability to articulate scientific concepts accurately, although utilizing diverse linguistic styles. In conclusion, this study posits that fishermen perceive the necessity of exploring alternative livelihoods that leverage their local knowledge. The expectation is that this approach can not only augment fishermen's income but also contribute to terubuk conservation endeavors.